2019
DOI: 10.2147/hiv.s226077
|View full text |Cite
|
Sign up to set email alerts
|

<p>Acceptance Of HIV Testing And Associated Factors Among Pregnant Women Attending Antenatal Care In Gunino Health Center, Southern Ethiopia 2019: An Institutional Based Cross-Sectional Study</p>

Abstract: Background: Acceptance of human immune virus testing is an entry point of intervention to end mother to child transmission of the virus among pregnant women. Methods: Institutional based cross-sectional study design with a sample size of 340 was conducted from May 20 to June 15, 2019. The data were collected by using systematic random sampling technique of interviewer administered questionnaire. Those candidate variables at bivariate analysis with a p-value <0.25 were moved to the multivariate logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
(20 reference statements)
1
8
0
Order By: Relevance
“…Studies conducted among eligible pregnant/postpartum women, infants and service providers were included in the analysis. Almost all the studies (44/52) were facility-based [ 23 , 25 , 39 , 45 , 58 62 , 64 74 , 76 89 , 91 93 , 95 101 ]. Furthermore, the study design varied across studies: cross-sectional studies (n = 28); prospective cohort (n = 2); retrospective cohort (n = 6), retrospective chart review (n = 4), qualitative studies (n = 8) and mixed methods studies (n = 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted among eligible pregnant/postpartum women, infants and service providers were included in the analysis. Almost all the studies (44/52) were facility-based [ 23 , 25 , 39 , 45 , 58 62 , 64 74 , 76 89 , 91 93 , 95 101 ]. Furthermore, the study design varied across studies: cross-sectional studies (n = 28); prospective cohort (n = 2); retrospective cohort (n = 6), retrospective chart review (n = 4), qualitative studies (n = 8) and mixed methods studies (n = 4).…”
Section: Resultsmentioning
confidence: 99%
“…Predisposing factors : Eight studies reported the presence of an association [ 25 , 57 , 59 , 63 , 64 , 66 , 95 , 103 ] and three studies [ 65 , 70 , 75 ] reported the absence of an association between educational level and maternal HIV testing. Of the eight studies that showed the presence of association, seven studies reported more educated women were found to be HIV tested than non-educated women [ 25 , 57 , 59 , 63 , 64 , 95 , 103 ]. Similarly, for women who have educated partners [ 57 , 103 ] and exposure to media [ 57 , 103 ] the odds of HIV testing were higher.…”
Section: Resultsmentioning
confidence: 99%
“…The positive influence of parity on attitude towards HIVST has been previously reported [36] and could be related to maternal experience and risk perception. Similarly, the positive influence of maternal education is expected, as it improves health literacy and risk perception which could facilitate precautionary action [18,37]. Likewise, employment empowers mothers, enhances the ability to pay and encourages healthy behaviour [18,38].…”
Section: Discussionmentioning
confidence: 99%
“…There is now a growing literature on financial incentives in various forms, such as conditional fixed incentives, prizes (e.g., lotteries), prize-linked savings accounts, cash transfer programs, conditional economic incentives, or some combination of these. 7,11,13,[28][29][30][31] HIV-related outcomes improved by financial incentives include HIV testing, HIV retesting, voluntary medical male circumcision (VMMC), and HIV prevention and treatment. [28][29][30][31][32][33][34][35][36] Our study contributes to this growing literature by examining the effect of financial incentives on HIV testing among pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Barriers for HIV testing may include lack of access to health care services, stigma and discrimination, perception of low transmission risk, lack of transportation or financial resources to visit an HIV testing facility, fear of a positive result and its socioeconomic implications, confidentiality issues, clinic setting, lower educational status, fear of not having access to effective treatment, and the lack of trained personnel in clinical encounters, among others. [6][7][8][9] Despite these barriers, improving HIV testing rates remains a priority because, according to the CDC, 40% of new HIV diagnoses can be linked to individuals unaware of their HIV status. 10 Incentives and insights from behavioral economics have been used to motivate health-affirming behaviors.…”
Section: Introductionmentioning
confidence: 99%